The Relationship Of Temporary Job Rotation And Nurse Work Stress - Rusdi, Rusdi; Mohd Said, Faridah; Umar, Nur Syazana (Journal of health research and technology, 2024)
Background: Work rotation does not always have a positive impact; productivity will decrease due to moving nurses to a new position, so there needs to be an adjustment again. In this type of temporary work rotation, there is a risk of problems because it is carried out in a relatively short period, and there is a lack of opportunity to adapt to a new environment, which can increase the work stress of nurses. Objective: To analyze the relationship between temporary work rotation and work stress of nurses in the Inpatient Hospital of the Hospital. Methods: Descriptive analytical research design with a cross-sectional approach, a total sample of 54 respondents selected using the Proportional Random Sampling technique. Results: The analysis test showed that as many as (53.7%) of respondents rated the temporary work rotation activity as "not good," and most of the respondents (70.4%) experienced "moderate" work stress. From the statistical test results obtained, p-value= 0.008 <0.05). Conclusion: There is a significant relationship between temporary work rotation and the work stress of nurses. Establish an appropriate policy regarding the appointment of officers and placement of work units according to their competence or clinical area, a schedule of rotation activities and a rotation process, a program of direction related to Rotation, and application of Rotation so that nurses are not bored and stressed